The Effect of Audit Committee Meetings, Profitability, and Foreign Ownership on Intellectual Capital - Nurainun Bangun; Ngadiman Ngadiman; Khairina Natsir (International Journal of Application on Economics and Business, 2023)
This study aims to obtain empirical evidence regarding the factors that affect intellectual capital in manufacturing companies listed on the Indonesia Stock Exchange during 2019-2021. The number of companies as the research sample was 34 manufacturing companies which were selected through purposive sampling technique with predetermined criteria. Intellectual capital is measured by Value Added Intellectual Coefficient (VAIC) taking into account VACA, VAHU, STVA. Panel data were processed using Eviews 12.0. Classical assumption testing includes multicollinearity test and heteroscedasticity test. Model selection is done by testing Chow, Hausman and Lagrange Multiplier. While the hypothesis test using the t test and the coefficient of determination test. The results of the analysis show that the audit committee frequency of meetings has a negative and insignificant effect on intellectual capital, Profitability as proxied by Return on Assets (ROA) has a positive and significant effect on intellectual capital, and Foreign ownership has a positive and significant effect on intellectual capital,